IN D'vision Sabah cultural ethnic heritage / Vun Fah Justin... [et al.] - Justin, Vun Fah; AK Banyang, Dissy Diana; Marcus, Cornellia; Suan, Nordin; Khalid, Iskandar (Faculty of Business Management, 2006)
The nature of our business we choose is on food and beverages. We are trying to focus on offering local traditional delicacies and not forgetting commercial menu to our beloved customer. As for additional purposes, we are trying to entertain our guest by giving them some kind of performance of course focusing as well on local culture such as performance on Sumazau Dance, Daling-Daling dance and many more to entertain them. As we all know, food and beverages industry have a very good opportunity to gain profit in the future as well as today. So in this case, we take these opportunities to establish a business with theme that introduce Sabah local traditional food together with the traditional performance to attract local and foreign tourist to come and experience the difference and uniqueness of our restaurant services that been offer publicly. The industry profile of our business that we want to establish is based on the food service provider but it has a theme that is on the cultural heritage of Sabah We choose this kind of business because beside the food service provider now develop very fast. We also have the opportunity to step inside the tourism industries that have good potential in Sabah to develop in the future because of the promotion by government and private sectors Other than that. Sabah also one of the place of interest in Malaysia that can attract visitor to come here and this is the reason why we come out with this type of business to catch the opportunities in the market.